Anesthetic management of a parturient with Guillain-Barre syndrome posted for emergency caesarian section - Abhijit Paul; Kasturi H Bandyopadhyay; Viplab Patro (Wolters Kluwer Medknow Publications, 2012)
We report the anesthetic management of a case of Guillain-Barre syndrome in the 34 th week of gestation coming for an emergency Cesarean section. The perioperative anesthetic challenges have been discussed with emphasis on the medical and anesthetic management which includes the use of plasma-pheresis, intravenous gamma-globulin, and the safety of preservative free 0.75% isobaric ropivacaine, which was administered intrathecally in this difficult medical condition with excellent hemodynamic, maternal, and fetal outcome. The sensory and motor blocks achieved were well suited to the clinical risks and conditions.